Pengaruh Indeks Persepsi Korupsi, Inflasi dan Nilai Tukar terhadap Investasi Asing Langsung di ASEAN-5 - Muhammad Cahya Purnama (Jurnal Ekonomi Aktual, 2022)
This study analyzes the effect of the corruption perception index (CPI), inflation, and the exchange rate on foreign direct investment (FDI) in ASEAN-5. The data used is secondary time-series data for 2005-2021, sourced from Transparency International and the World Bank. Data were analyzed using panel data regression. The study results show that CPI, inflation, and the exchange rate significantly affect FDI in ASEAN-5. Partially the corruption perception index and the exchange rate have a significant effect on FDI in ASEAN-5, while inflation has no significant effect.